EVALUATION OF CLINICAL BIOCHEMISTRY OF BLOOD IN BITCHES AFFECTED WITH PYOMETRA - GUPTA, A K; DHAMI, A J; PATEL, S B; SHAH, R G (The Indian Journal of Animal Reproduction, 2023)
Nine pyometric and eight healthy bitches were included to evaluate their plasma biochemical, enzymatic and sex steroid profile before and after ovario-hysterectomy. The pre-operative levels of plasma urea nitrogen (PUN), creatinine and total cholesterol were significantly (P<0.01) higher in pyometric bitches than the normal ones (60.78±10.03 vs 16.75±1.58 mg/di; 2.71±0.51 vs 0.85±0.10 mg/di and 256.52±25.19 vs 189.00±8.91 mg/di, respectively). The post-operative levels of all three constituents, particularly PUN and creatinine, declined in cases of pyometra. Plasma total protein (7.67±0.61 vs 5.70±0.28 g/dl) and globulin (5.29±0.41 vs 2.30±0.13 g/dl) concentrations were significantly (P<0.01) higher and albumin (2.38±0.22 vs 3.40±0.28 g/dl) concentration was lower in pyometric bitches than the healthy ones, thus significantly (P<0.01) reducing the albumin-globulin ratio (0.45±0.02 vs 1.52± 0.15) in pyometra affected bitches. The pre-operative mean aspartate and alanine aminotransferase (AST, ALT) and alkaline phosphatase (ALP) activities were significantly higher (P<0.01) in bitches affected with pyometra (66.33 ± 9.84 and 73.78 ± 8.78 IU/I, and 86.78 ± 13.20 KAU %, respectively) as compared to healthy ones (32.50 ± 1. 70, 31.25 ± 1.46 IU/1 and 40.13 ± 2.59 KAU %). The levels of ALP were insignificantly higher in cases of closed pyometra than the open ones, but not of AST or ALT. The levels of all 3 enzymes dropped a little by 8-15 days following surgery in affected animals. Plasma progesterone profile was three times elevated (11.20 ± 2.88 vs 4.1 O ± 0.91 ng/ml) and oestradiol-17b was insignificantly reduced (623.78 ± 235.75 vs 777.38 ± 174.02 pg/ml) in pyometric bitches than the normal ones. Moreover, the mean progesterone concentration was significantly higher in cases of closed pyometra than the open ones (19.97 ± 2.88 vs 6.81 ± 2.59 ng/ml), and it declined significantly within 8-15 days following ovario-hysterectomy. It was concluded that significant elevation in serum biochemical and enzymatic profile together with progesterone in pyometric bitches as compared to normal ones with the drop in their levels post-operatively is of diagnostic and prognostic value in canine pyometra.